The VIPs of Wolf Conservation: How Values, Identity, and Place Shape Attitudes Toward Wolves in the United States - Carlson, Shelby C.; Dietsch, Alia M.; Slagle, Kristina M.; Bruskotter, Jeremy T. (Frontiers in Ecology and Evolution, 2020)
Attitudes toward wildlife shape support for and opposition to myriad conservation actions worldwide. Scholars have long debated what are the most critical factors shaping these attitudes, and research on carnivores has often treated important factors such as values, identity, and place, as independent of one another. To better integrate these factors in the context of explaining attitudes toward wolves (Canis lupus), we explore the effect of: (i) region of the U.S. (Northern Rocky Mountains, Western Great Lakes, and the remainder of the country), (ii) sociodemographic characteristics (age, gender, income, urban/rural residency, and education), (iii) indicators of one's social identity (hunter, farmer, environmentalist, and animal rights advocate), and (iv) wildlife value orientations (mutualism and domination). Using one-way analysis of variance tests and hierarchical regression analyses, we found that attitudes do not statistically differ across regions with wolves (compared to regions without wolves), yet the people who identify with interest groups most likely to directly impact or be impacted by wolf populations, such as farmers/ranchers, are less tolerant of wolves when they live closer to them (i.e., in the Northern Rocky Mountains and Western Great Lakes) even when accounting for individual-level values. By examining attitudes toward wolves at a spatial scale not commonly assessed, this study seeks to enhance current understandings of the impact of values, identity, and place, while serving as a guide to inform future research and policies regarding carnivore management.